SULTAN MEHMED VAHİDEDDİN ŞARKILARININ TÜR VE BİÇİM YÖNÜNDEN ANALİZİ - BULUT, CEMİL HADİ (Fırat Üniveristesi, 2018)
Fırat Üniversitesi Sosyal Bilimler Enstitüsü Müzik Anabilim Dalı'nda hazırlanmış olan bu yüksek lisans tezinde, Osmanlı Devleti'nin son padişahı Sultan Mehmed Vahideddin, siyasî kimliğinden ziyade "İcracı-Bestekâr Mehmed Vahideddin" olarak ele alınmıştır. Sultan Vahideddin'in yetmiş bir sene boyunca ailesi tarafından muhafaza edilmiş olan besteleri arasından, bestekârlığını ön plana çıkaran ve Türk Müziğinin dizi ve seyir bakımından zengin makamlarından meydana gelen on tanesi bu çalışmada biçim ve tür yönünden incelenmiştir.

Mehmed Vahideddin, last Sultan of Ottoman Empire takes part in this graduate thesis prepared in institute of social sciences music majör at Fırat University as a instrumentalist – composer Mehmet Vahideddin, not as a politic person. Among the compositions protected by his family for 71 years, ten of them consisting of the modes which reflects his composer side have been reviewed as form and genre. These ten compositions have been reviewed as from and genre because they where composed with the modes which are used more and rich about scale and improvization in Turkish music.
The kind and form analysis of Sultan Mehmed Vahdettin's pieces composed in the form of a song
Keywords: Müzik